Millennials’ purchase intention of cruelty-free cosmetics : the mediating and moderating effects of attitude, altruism and knowledge - Gris, Mariana (2023)
Cruelty-free cosmetics tend to evoke highly favourable attitudes and behaviours. Indeed, the millennial generation, recognised as the largest and most influential consumer segment, has driven a shift towards more conscientious consumption, notably in the demand for ethical cosmetics. Consequently, to enhance consumer appeal, companies are increasingly exploring certification label attributes that symbolise their abstaining commitment from animal testing. This research strives to understand millennials’ intention to purchase cruelty-free cosmetics, emphasising the mediating effect of attitudes towards cruelty-free cosmetics, and the moderating effects of both consumers altruism and knowledge of such cruelty-free labels, utilising a moisturiser cream as an example. The study employed an exploratory sequential mixed method, combining a focus group for stimulus development with an online questionnaire featuring three stimuli randomly assigned to each respondent. Key findings indicate that the presence of a cruelty-free logo significantly influences consumers’ purchase intention, with certified cruelty-free logos yielding more positive intentions to purchase compared to uncertified logos. However, the results suggests that neither attitude serves as a mediator nor knowledge and altruism act as moderators in the model. In conclusion, this study provides cosmetic brands’ managers and marketers with valuable insights on enhancing consumers purchase intention, by incorporating cruelty-free labels, particularly those certified by independent entities.